2022
DOI: 10.1111/jbfa.12591
|View full text |Cite
|
Sign up to set email alerts
|

Do liquid assets lure managers? Evidence from corporate misconduct

Abstract: We examine the effect of asset redeployability on corporate misconduct and find a significant positive relationship.Utilizing a large sample of public US firms for the period of 2001 to 2015, we find that a one standard deviation (SD) increase in the proportion of redeployable assets leads to a 7.2% increase in corporate fines. We also find that the positive association between asset redeployability and corporate misconduct varies across types of misconduct and industrial heterogeneity. In our channel analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…Environmentally irresponsible events impede firm cash flows and market value (Lin et al, 2016; Zaman et al, 2022a) and investors, especially the buy‐and‐hold investors, react to higher TCR reporting, considering it detrimental to their investment, by causing a DOWN trend in the market and thus increasing IRV; whereas the lower TCR reporting results in an UP market trend and results in lower IRV of the firm. According to our results, as reported in Table 8, the relation between TCR and IRV is more pronounced in the DOWN market state (β = 0.015, p < 0.05 and β = 0.015, p < 0.05, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Environmentally irresponsible events impede firm cash flows and market value (Lin et al, 2016; Zaman et al, 2022a) and investors, especially the buy‐and‐hold investors, react to higher TCR reporting, considering it detrimental to their investment, by causing a DOWN trend in the market and thus increasing IRV; whereas the lower TCR reporting results in an UP market trend and results in lower IRV of the firm. According to our results, as reported in Table 8, the relation between TCR and IRV is more pronounced in the DOWN market state (β = 0.015, p < 0.05 and β = 0.015, p < 0.05, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The literature has utilised a deductive approach using archival data and quantitative methods to identify factors that influence firms to engage in CSIR (Jain & Zaman, 2020; Shao et al, 2021; Zaman et al, 2021; Zaman et al, 2022). However, given limited archival data on CSIR, a growing number of studies have adopted qualitative approaches to examine CSIR (Herzig & Moon, 2013; Küberling‐Jost, 2019; Riera & Iborra, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the behavioural aspect could provide further explanations for why individual agents, organisations, and institutions follow certain paths. The literature has shown that behavioural aspects play important roles in determining how and why organisations engage in CSIR (Campbell, 2007, 2018; Cohen et al, 2011; Jain & Zaman, 2020; Zaman et al, 2021; Zaman et al, 2022). Hence, we extend Küberling‐Jost (2019) by integrating three behavioural theories that correspond to the micro, meso, and macro levels into the path dependence theory.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations